Perancangan Sistem Pemantauan Suhu dan Kelembaban pada Proses Dekomposisi Pupuk Kompos berbasis IoT - Hardyanti, Farida; Utomo, Pramudi (Elinvo (Electronics, Informatics, and Vocational Education), 2019)
The problem that often occurs in making compost is the level of fertilizer maturity that is not perfect. This is caused by humidity and temperature in the unstable manufacturing process. This article aims to develop a system capable of controlling temperature and humidity as well as monitor changes in the process of compost decomposition wirelessly and describe the results of testing the system. This research uses a development method with several stages, namely: problem identification and needs analysis, design, implementation, and testing. The results show that: (1) a temperature and humidity monitoring system is realized to monitor and regulate the process of making IoT-based compost by utilizing DHT-22 sensor input as a temperature and humidity detector and sensor to detect the pH content of compost processed using Wemos D1 mini. Output data that has been obtained will be sent to the Android smartphone application and in the form of a relay that will activate the heater and cooler as a temperature stabilizer; and (2) the test results show that performance is appropriate, which by manual means has the advantages of: (a) more efficient 2 to 4 weeks; and (b) has automatic and manual control.